Current AAV-mediated gene therapy in sensorineural hearing loss - Jieyu Qi; Xiaolong Fu; Liyan Zhang; Fangzhi Tan; Nianci Li; Qiuhan Sun; Xiaojie Hu; Zuhong He; Ming Xia; Renjie Chai (Fundamental Research)
The number of patients with hearing loss is on the rise due to congenital abnormalities, degenerative changes in old age, and acquired injuries such as virus or ototoxic drug-induced diseases. Hearing loss is a refractory and disabling disease that has serious negative effects on quality of life. The pathology of hearing loss in the inner ear is characterized by varying degrees of damage to the cochlear sensory epithelium cells (such as hair cells and supporting cells), stria vascularis (including marginal, intermediate and basal cells) and spiral ganglion neurons. Regeneration or direct repair of damaged cells in the inner ear is an effective way to treat sensorineural deafness. It is currently possible to regenerate hair cells to treat sensorineural hearing loss by FX-322, a small molecule drug in clinical trials. With the development of genetic engineering technology, gene therapy has brought a promising treatment strategy for many previously intractable diseases. Gene therapy has been regarded as a promising method in the treatment and rehabilitation of sensorineural hearing loss, and recombinant adeno-associated virus gene therapy has been widely used in fundamental research into hearing loss treatments. At present, gene therapy for hearing loss is transitioning from feasibility studies to explorations of its safety and its therapeutic potential. The present article reviews the concepts, strategies, and applications of gene therapy mediated by recombinant adeno-associated viruses in the field of hearing loss treatment.